2019
DOI: 10.1590/s2175-97902019000217497
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sonication and in vitro evaluation of nifedipine self-nanoemulsifying drug delivery system

Abstract: In order to develop a self-nanoemulsifying system, three components, olive oil, Tween 80, and Capmul, were used to construct a ternary phase diagram that helped to find the optimum formulation, which was loaded with nifedipine. The effect of sonication on drug loading was also evaluated. After that, measurement of the droplet size, size distribution, zeta potential, and scanning electron microscopy were conducted for evaluation and characterisation of the formulations. The phase diagram of four formulations sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…The results of globule size analysis using a particle size analyzer showed that CLO-SNEDDS (F2D) was able to form a nanoemulsion system after dilution with a globule size of 125 nm and a PDI value of 0.515. These results followed the globule size requirements for SNEDDS (20-200 nm) and PDI of <0.7 30 .…”
Section: Resultssupporting
confidence: 71%
“…The results of globule size analysis using a particle size analyzer showed that CLO-SNEDDS (F2D) was able to form a nanoemulsion system after dilution with a globule size of 125 nm and a PDI value of 0.515. These results followed the globule size requirements for SNEDDS (20-200 nm) and PDI of <0.7 30 .…”
Section: Resultssupporting
confidence: 71%
“…These results demonstrate that the higher long-term stability of honokiol PLGA − PEG nanoparticles when stored at 4 °C allows them to maintain good drug content in the nanocarrier. In addition, some studies recommend storing drug-carrying nanoparticles at 4 °C [38,41].…”
Section: Encapsulation Efficiency and Loading Capacity Of Honokiol Pl...mentioning
confidence: 99%
“…Crystal engineering is a method to design a crystalline molecular solids with the aim of impacting material properties [10]. In recent years, the advances in crystal engineering have emerged in the research for design of pharmaceutical cocrystals which consists the API and another compound (called co-former) at a given stoichiometric ratio [11].…”
Section: Introductionmentioning
confidence: 99%